2006
DOI: 10.22621/cfn.v120i1.241
|View full text |Cite
|
Sign up to set email alerts
|

Conditions for Sexual Interactions Between Wild Grey Wolves, <em>Canis lupus</em>, and Coyotes, <em>Canis latrans</em>

Abstract: Genetic evidence for the hybridization of wild Grey Wolves and Coyotes was first reported by Lehmann et al (1991). Subsequent genetic and landscape-environmental analyses have attempted to grasp the extent of Wolf-Coyote crosses in North America. Since Wolves are normally territorial and thus aggressive towards Coyotes, hybridization events remain rare, not withstanding the taxonomic debates regarding Canis in eastern Ontario. In this paper I report on amicable interactions between Wolves and Coyotes observed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…The one exception is a report of wolves and coyotes traveling together, although no hybrids were known to have resulted from them (Thiel 2006).…”
Section: Resultsmentioning
confidence: 99%
“…The one exception is a report of wolves and coyotes traveling together, although no hybrids were known to have resulted from them (Thiel 2006).…”
Section: Resultsmentioning
confidence: 99%
“…Aggressive interactions between wolves and coyotes have been reported in Wisconsin, including the killing of coyotes by wolves (Thiel 2006), but reports also exist of genial behavioural interactions between wolves and coyotes in Wisconsin (Thiel 2006), presenting the possibility for sexual interaction between them. Maternal and paternal genetic markers indicate the low‐level introgression of wolf (or dog; Y chromosome only) genes in coyotes in the WGLR, but this may reflect past hybridization and is not consistent with ongoing gene flow, which appears minimal (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…For example, studies routinely report that gray wolves ( Canis lupus ) and coyotes are reproductively isolated in the wild (García‐Moreno, Matocq, Roy, Geffen, & Wayne, ; Hohenlohe et al., ; Kyle et al., ; Pilgrim, Boyd, & Forbes, ; Rutledge, Wilson et al., ; Wheeldon, Patterson, & White, ), although it has been suggested that the two species do hybridize (vonHoldt et al., , ; vonHoldt, Cahill et al., ). Gray wolf and coyote interactions are well documented throughout North America and, despite routinely interacting ecologically as sympatric species (Arjo, Pletscher, & Ream, ; Atwood & Gese, ; Switalski, ), amicable consorting behavior between them is extremely rare (Hohenlohe et al., ; Thiel, ). To our knowledge, congeneric pairings between gray wolves and coyotes have not been confirmed in field studies.…”
Section: Introductionmentioning
confidence: 99%